Pengembangan Aplikasi Pembentukan Kelompok Cooperative Learning Menggunakan Visual Basic - Agus Prasetyo Kurniawan (JRPM (Jurnal Review Pembelajaran Matematika), 2016)
This study aim to develop an application using visual basic programming to facilitate the formation of cooperative groups and to investigate the validity, effectiveness, and practicality of the development of this application. This research method including R&D performed with 6 stage, consists of: the potential and problems, data collection, product design, design validation, improved of design, and test products. The results showed that the yield of the IT media expert validation amounted to 82.5% and validation of learning experts is 92.86%. In addition, the results of the questionnaire responses test of subjects each amounted 83.33% for the first test subjects and 91.67% for the second test subjects. Seeing these findings, it can be concluded that the application of cooperative learning group formation using visual basic can be said to be very feasible to be used as a tool for the establishment of cooperative learning groups.